Are bank capital requirements optimally set? Evidence from researchers' views - Gene Ambrocio; Iftekhar Hasan; Esa Jokivuolle; Kim Ristolainen (Bank of Finland, 2020)
We survey 149 leading academic researchers on bank capital regulation. The median (average) respondent prefers a 10% (15%) minimum non-risk-weighted equity-to-assets ratio, which is considerably higher than the current requirement. North Americans prefer a significantly higher equity-to-assets ratio than Europeans. We find substantial support for the new forms of regulation introduced in Basel III, such as liquidity requirements. Views are most dispersed regarding the use of hybrid assets and bail-inable debt in capital regulation. 70% of experts would support an additional market-based capital requirement. When investigating factors driving capital requirement preferences, we find that the typical expert believes a five percentage points increase in capital requirements would 'probably decrease' both the likelihood and social cost of a crisis with "minimal to no change" to loan volumes and economic activity. The best predictor of capital requirement preference is how strongly an expert believes that higher capital requirements would increase the cost of bank lending.
URN:NBN:fi:bof-202006012160
Keywords: G01; G28; 330; Bank regulation; capital requirements; expert survey